STUDIES ON FROZEN STORAGE OF CUTTLE FISH FILLETS - JOSEPH, JOSE; PERIGREEN, P A (Fishery Technology, 2017)
The freezing and cold storage characteristics of cuttle fish :fillets have been studied. The yield of fillets from cuttle fish was about 35 /'~and the fiUet had an average moisture content of 76.85 % and fat D.82 %- During storage at -20 + 1Â°C for 16 months the salt soluble nitrogen of the fillets decreased from 85.1to35.36 Â the non-protein nitrogen from 24.61 to 20.84 % and alpha amino nitrogen from 252 to 140 mg/100 g. Initially the fillets were white in colour, showed signs of desiccation by 4 months storage which increased on further storage and the fillets finally became dull white with yellow discolouration inside. The firm and chewy texture of the cooked fillets changed to rubbery even though the product was slightly sweet at the end oftht storage period of 16 months.